Distribution of plantparasitic nematodes on Musa in Kenya - Reddy, K.S.; Prasad, J.S.; Speijer, P.; Sikora, R.A.; Coyne, Danny L. (2007)
In 1990, observations were made on the nematode species profile on bananas in Oyugis district, Kenya. The country-wide survey was conducted in 1993 across 13 primary Musa growing districts. Observations were made on banana cultivars Nakyetengu (AAA) and Sukali Ndizi (AB). Considerable variation in nematode densities between farms within Oyugis district was observed with Pratylenchus goodeyi present at higher densities than other nematodes. Radopholus similis was observed on 3 of the 6 farms on Nakyetengu, but at none on Sukali Ndizi, while Meloidogyne spp. (second stage juveniles) were observed on Sukali Ndizi on all farms, but on only 3 farms on Nakyetengu. P. goodeyi was widespread on EAHB in most districts surveyed, except Busia near the Ugandan border and at Kwale at the coast. In both the low altitude coastal districts of Kwale and Kilifi, however, P. goodeyi was observed on exotic bananas. The presence of R. similis was limited to Oyugis and Homa Bay districts only. In Kwale and Kilifi, Helicotylenchus multicinctus and in Kilifi Meloidogyne spp. were recorded only from exotic banana cultivars and not EAHB. In Muranga district, P. coffeae was extensively recovered from both EAHB and exotic banana and was also recorded on exotic bananas in Nyeri and Vihiga districts. The nematodes Rotylenchus clavicaudatus, Scutellonema spp., Criconema spp., Xiphinema spp., Hemicycliophora spp. and an undescribed species of Trophurus were also observed infrequently.